Kombinasi keong mas dan ikan rucah sebagai pakan kepiting bakau (Scylla serrata) - Novandi, Bagoes; Linggi, Yulianus; Sunadji, Sunadji (Jurnal Aquatik, 2023)
Mud crab (S. serrata) is known as a fishery commodity with high economic value. Mangrove crabs are naturally omnivorous, eating various types of organisms that live in the mangrove ecosystem such as decaying leaves, algae, roots, nuts, toads, snails, shrimps, clams, dead animals and fish. This study used gold snail combined with ikan rucah as feed to determine the percentage of the best combination in feed on the growth and survival of mangrove crabs (S. serrata). A completely randomized design was used and consisted of three treatments and three replicates, namely the provision of gold snail and small fish with a percentage ratio: (a) 25:75, (b) 50:50 and (c) 75:25. The results showed that the highest crab growth (absolute weight) was 46.63 g when fed with gold snail and fish waste in the ratio of 25:75 while the growth in the 50:50 and 25:75 treatments was only 31.23 g and 31.31 g, respectively. The results of this study then concluded that gold snails can trigger the growth of mud crabs if the portion is less than the main food in the form of fishmeal.